The effects of globalization on artisanal fisheries in the magellan and chilean antarctic region - Morales Camacho, María Fernanda (University of Amsterdam, 2018)
MSc International Development Studies (Research) Maestría en Estudios de Desarrollo Internacional (Investigación) Globalization and changes in international markets have effected the local level by defining and redefining the local production schemes, excluding or including actors, transforming local cultures, and influencing the ecosystems’ sustainability. While there is vast literature about local and global economic interactions and value chains of various fisheries, there are no studies on the value chain and socioeconomic issues of the southern king crab. Therefore, this research aims to understand the consequences of global fishing markets on the Magellan and Chilean Antarctic regions by studying the history and value chain of this fishery and the effects of global value chains (GVC) on the social well-being of those artisanal fishers involved in this activity. A mixed-methods approach was applied, employing observations, semi-structured and unstructured in-depth interviews, and a survey with the fishers and key informants. This study finds a simplification in the production requirements due to the new markets’ preferences oriented in less processed seafood. One of the main buyers, China, has influenced the transformations in the production process by buying whole frozen products instead of canned food. However, despite a lower added value, the prices paid for this marine resource are higher than in the past due to the increasing demand and hard competition among suppliers. This increase in price influences the social mobility and the objective well-being of the fishers and differentiates this activity from other Chilean fisheries because of the income. The king crab’s case deepens the knowledge about the complexity in fisheries’ structures and highlights the social dimensions of them. By showing how globalization and globalization of fisheries have developed highly regulated and competitive artisanal fishing activity, this study shows the importance of complementing the predominantly technical and ...